The dog that didn’t bark? The 2010 Quadrennial Defence Review - Bitzinger, Richard A. (2011)
The Department of Defence’s long-awaited Quadrennial Defence Review offers little new when it comes to discussing the future direction of the US military. More notably, it hardly mentions the